Spillovers from tax shocks to the euro area - Sascha Mierzwa (Philipps-University Marburg, School of Business and Economics, 2021)
I study the spill-over effects of legislated discretionary tax changes in the United States, Germany, and the United Kingdom to 11 Eurozone countries for the period 1980Q1-2018Q4 employing Local Projections (Jordà, 2005). In general, I find spillovers from US tax legislation to have the smallest effects on Eurozone countries' real GDP and UK tax changes to exert the largest effect. There is substantial heterogeneity in both the sign and size of spillovers after US and German aggregated tax cuts, whereas UK tax cuts generally have beneficial effects. When I focus the analysis on the statedependent case, I do not find clear evidence of larger spillovers when the recipient country is in a recession. The sign and size of the spillovers instead depend on the origin and sign of the tax change, as well as the recipient country, rather than on the overall state of the business cycle. Moreover, German tax cuts can be contractionary when recipient countries are in a recession, as the short-term interest rate rises. US tax cuts, on the other hand, stimulate the exports of most countries regardless of the state of the business cycle.
Keywords: E62; E63; F45; H20; H30; K34; 330; Fiscal policy; tax policy; legislated tax changes; state dependence; Eurozone; fiscal spillovers; asymmetric effects; United States; Germany; United Kingdom; local projections; narrative approach